Development of supine and standing knee joint position sense tests. (May 2021) - Strong, Andrew; Srinivasan, Divya; Häger, Charlotte K.
Abstract: Objectives: We aimed to assess the test-retest reliability of a supine and standing knee joint position sense (JPS) test, respectively, and whether they discriminate knees with anterior cruciate ligament (ACL) injury from asymptomatic knees. Design: Repeated measures and cross-sectional. Setting: Research laboratory. Participants: For test-retest reliability, 24 persons with asymptomatic knees. For discriminative analysis: 1) ACLR - 18 persons on average 23 months after unilateral ACL reconstruction, 2) CTRL - 23 less-active persons, and 3) ATHL - 21 activity level-matched athletes. Main outcome measures: Absolute error (AE) and variable error (VE). Results: Test-retest reliability was generally highest for AE of the standing test (ICC 0.64–0.91). Errors were less for the standing compared to the supine test across groups. CTRL had greater knee JPS AE (P = 0.005) and VE (P = 0.040) than ACLR. ACLR knees showed greater VE compared to the contralateral non-injured knees for both tests (P = 0.032), albeit with a small effect size (ηp 2 = 0.244). Conclusions: Our standing test was more reliable and elicited lesser errors than our supine test. Less-active controls, rather than ACLR, produced significantly greater errors. Activity level may be a more predominant factor than ACLR for knee JPS ∼2 years post-reconstruction. Highlights: Our standing knee JPS test had higher reliability than our supine test. ACLR knees had greater variable error than contralateral non-injured knees. Less-active controls had greater errors than individuals with ACL reconstruction. Assessment of knee JPS after ACL reconstruction should consider activity level.